2014
DOI: 10.1155/2014/425321
|View full text |Cite
|
Sign up to set email alerts
|

Pain‐Related and Negative Semantic Priming Enhances Perceived Pain Intensity

Abstract: Verbal priming plays a role for the perception of noxious stimuli in a time-dependent manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
23
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 50 publications
(81 reference statements)
6
23
1
1
Order By: Relevance
“…Non‐painful stimulation cued by sensory pain words resulted in higher intensity ratings than non‐painful stimulation cued by neutral words did. These findings align with other evidence that painful visual primes elicit comparatively higher intensity ratings of somatosensory stimuli (e.g., Dillmann et al., ; Meng et al., ; Richter et al., ), perhaps due to pre‐activating neural networks subserving pain memory and pain processing. Slower RTs in judging non‐painful stimulation cued by sensory pain words rather than neutral words may have illustrated a general interruptive function of pain cues on task‐related cognitive processing (e.g., Eccleston & Crombez, ; Van Damme et al., ) or effects of incongruent expectations in trials featuring painful visual primes and non‐painful stimulation (e.g., Fazio, ; Wiech, ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Non‐painful stimulation cued by sensory pain words resulted in higher intensity ratings than non‐painful stimulation cued by neutral words did. These findings align with other evidence that painful visual primes elicit comparatively higher intensity ratings of somatosensory stimuli (e.g., Dillmann et al., ; Meng et al., ; Richter et al., ), perhaps due to pre‐activating neural networks subserving pain memory and pain processing. Slower RTs in judging non‐painful stimulation cued by sensory pain words rather than neutral words may have illustrated a general interruptive function of pain cues on task‐related cognitive processing (e.g., Eccleston & Crombez, ; Van Damme et al., ) or effects of incongruent expectations in trials featuring painful visual primes and non‐painful stimulation (e.g., Fazio, ; Wiech, ).…”
Section: Discussionsupporting
confidence: 90%
“…Compared to neutral words, sensory pain words have been found to elicit elevations in subjective pain intensity (Richter et al., ), larger N2 and P2 amplitudes vis a vis laser‐evoked potentials (LEPs) in chronic pain patients (Weiss, Miltner, & Dillmann, ), and larger P370 amplitudes among pain‐free adults (Dillmann, Miltner, & Weiss, ). However, because FOP was not examined in these studies, it is not clear whether specific neural signatures that correspond to the processing of pain word cues also discriminate less from more trait pain‐fearful subgroups.…”
Section: Introductionmentioning
confidence: 99%
“…For example, studies by Pulvermüller et al (Pulvermuller, ; Pulvermüller & Fadiga, ) showed that the presentation of action words such as singing and throwing not only activated semantic memory networks but simultaneously also representations of the mouth or arm in the primary motor cortex indicating that language might be embodied. Based on TNN and the theory of language embodiment, Richter and colleagues observed similar effects to pain‐related words that induced pain sensations although no painful stimuli were presented (Eck, Richter, Straube, Miltner, & Weiss, ; Richter et al, , ).…”
Section: Introductionmentioning
confidence: 95%
“…For example, studies by Pulvermüller et al (Pulvermuller, 1999;Pulvermüller & Fadiga, 2010) showed that the presentation of action words such as singing and throwing not only activated semantic memory networks but simultaneously also representations of the mouth or arm in the primary motor cortex indicating that language might be embodied. Based on TNN and the theory of language embodiment, Richter and colleagues observed similar effects to pain-related words that induced pain sensations although no painful stimuli were presented (Eck, Richter, Straube, Miltner, & Weiss, 2011;Richter et al, 2010Richter et al, , 2014. Thus, specific predictions are possible for the priming effects evoked by negative versus pain-related words compared with neutral words: Elevated pain ratings and stronger cortical activation should be observed when pain-related and negative words compared with neutral words would be used as primes preceding or during painful stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…Negative affective and pain-related cues may be an ongoing process in chronic pain patients (Richter et al, 2014). Thus, subconscious emotional and sensory aversion may contribute to maintaining the pain state.…”
Section: The Tipping Point: Neurobiological Processes Brain Dysfumentioning
confidence: 99%